ANALISIS PENGEMBANGAN LAYANAN PENDIDIKAN INKLUSIF BERBASIS EKONOMI KREATIF DI KABUPATEN BANYUWANGI - Muhamad Alfi Khoiruman; Galih Satriyo (Jurnal Education and Development, 2022)
The purpose of this study is to identify existing conditions, inhibiting factors and identify the right model to support inclusive education based on creative economy. The research method used is a qualitative approach. The informants of this research are the Education Office, the Branch of the Education Office of East Java Province, Banyuwangi Regency, Special Advisor Teachers, PLB Supervisors and Micro Business Actors. The results of the study revealed that the implementation of the curriculum used in the implementation of learning implemented by inclusive schools in Banyuwangi had adjusted to the needs of children with special needs. The obstacle for inclusive schools is that most inclusive schools are still struggling academically and have not prepared for the independence of the world of work, because inclusive schools tend to be for students with special needs who have hopes of going to a higher level of education. Meanwhile, vocational education for children with special needs tends to be in special schools. The absence of special educators in the creative economy and training carried out by the government through micro-enterprises is not sustainable. The right model used in the implementation of creative economy-based inclusive education in Banyuwangi Regency is by pioneering a double track inclusive school that combines academic and vocational activities as well as cooperate with micro business actors considering that Banyuwangi micro business actors have various types of business fields such as batik, souvenirs and culinary.